Strategic Management of Kauman Tourism Village in Supporting the Development of Menara Kudus Religious Tourism - Risnanda Ines Priadyantika; Khasan Setiaji (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2026)
The development of religious tourism at the Menara Kudus requires strategic support from the Kauman Tourism Village. Although it has strong cultural, historical, and religious potential, its management still faces limitations in human resources, suboptimal institutional coordination, and unsustainable utilisation of local potential. This study aims to analyse management, identify internal and external factors, and formulate strategies using SWOT analysis. The method used is qualitative descriptive with data collection techniques through observation, interviews with 10 informants, and documentation. The data were analysed using IFAS, EFAS, IE Matrix, and SWOT. The results show that Kauman Tourism Village is in Quadrant V (hold and maintain), indicating a stable condition with internal strengths and supportive external opportunities, but still requiring governance strengthening to avoid stagnation. Research findings confirm that the sustainability of tourist destinations is determined by the effectiveness of collaboration between the village government, Pokdarwis, area managers, and the community within the framework of community-based tourism. Priority strategies include strengthening institutions, enhancing human resource capacity, optimising digital promotion, and technology-based visitor management. This research contributes to strengthening a village tourism management model based on institutional collaboration to support sustainable religious tourism.